Frequency and Resistance Pattern to Enterobacteriacae - Fakhruddin Abid Hussain Chang , Razi uddin Ahmed , Mohammad Asif Durrani (Journal of Rawalpindi Medical College, 2014)
Background To determine the frequency of Enteriobacteriaceae species and resistance pattern from clinical isolates Methods: In this descriptive study,500 samples were collected from the patients showing signs and symptoms of bacterial infection and isolates were screened for primary selection. These specimens (n=500) were divided into four groups: (a) 200 samples of urine were taken from UTI suspected patients, (b) 150 samples of pus were taken from wounds, irrespective of its site, (c) 100 samples were taken from respiratory tract (tracheal aspirates and sputum) and (d) 50 samples of blood were taken from suspected patients of septicemia. After overnight incubation, established microbiological methods, which included colonial morphology, gram’s staining and biochemical characteristics were used for identification. E. coli ATCC 25922 was used as quality control strain for the antimicrobial sensitivity.Antimicrobial susceptibility testing of the isolated organisms was performed by the disk diffusion technique. Results: From amongst (402) organisms, 200 (49.75%) turned out to be Enterobacteriaceae while Escherichia coli was leading pathogen (65%). There was an increase in resistance against cephalosporin 3rd and 4th generation (upto74%). The lowest resistance was observed against Amikacin and Carbapenems. Conclusion: There is a surge of infections caused by Enterobacteriaceae and resistant strains are also increasing.